Exploratory study of the terms “plantio direto” and “semeadura direta” and their variations in bibliographic databases (Research, Society and Development, 2020)
When used in regions with different edaphoclimatic conditions than those in the southern region of Brazil, where it was developed, the premises of a system could not always be met with the practice of the “sistema plantio direto”, however, this nomenclature was often maintained, which has caused confusion in its diffusion and difficulty in comparing scientific researches. The objective of this work was to evaluate the variations in which the terms "plantio direto" and "semeadura direta" have been used in publications deposited in bibliographic databases on the internet. To this end, an exploratory research was applied, whose results were quantitatively analyzed. The investigation included searches of the terms “plantio direto”, “semeadura direta” and variations of these, to the databases of the Brazilian Digital Library of Theses and Dissertations, Catalog of Theses and Dissertations of CAPES, Google Scholar, Revista Brasileira de Ciência do Solo - RBCS and Scientific Eletronic Library Online - SciELO. The wide variation in the use of the terms “plantio direto” e “semeadura direta” was proven, with the former having a greater occurrence in all the databases consulted. The databases that represent publications exclusively in scientific journals, presented lower percentages of occurrence of the term “sistema” preceding the terms "plantio direto" and "semeadura direta". This study suggests the realization of others that can assess the correct application of the term "sistema", associated with the term "plantio direto" in papers.